Fibrous Dysplasia: From Historical Approaches to Modern Treatment Perspectives - Zyma, A.M.; Skuratov, O.Iu.; Huk, Yu.M.; Filipchuk, V.V.; Cheverda, A.I.; Kincha-Polishchuk, T.A.; Melnyk, M.V.; Suvorov, V.L. (TERRA ORTHOPAEDICA, 2025)
Objective. This study aims to analyze scientific literature on fibrous dysplasia (FD) and highlight the state of diagnosis and treatment of orthopedic pathology in patients with various forms of FD.Materials and Methods. This article is based on a retrospective review of papers by various authors on the treatment of patients with FD. Articles were selected from scientific databases such as SCOPUS, Web of Science, and Google Scholar. The selected articles were reviewed in chronological order according to the topic of the study.Results and Discussion. The article provides a systematic analysis of treatment approaches for patients with FD at different stages of the development of science. Modern diagnostic and therapeutic approaches are also analyzed, with particular attention given to the molecular-genetic aspects of the disease’s etiology, particularly mutations in the GNAS gene, which underlie bone growth regulation disorders. Current treatment approaches, including the use of bisphosphonates and various types of surgical interventions, are discussed.Conclusions. A review of the scientific literature and analysis of historical aspects related to FD indicate both significant achievements of the orthopedic community in the diagnosis and treatment of FD, as well as significant challenges that will require further resolution. Changing views on the etiology and pathogenesis of the disease, as well as the identification of genetic mutations during early fetal development, have led to the recognition of FD as a stem cell disease. This provides new leverage for doctors and researchers to use stem cells in the treatment of patients with this pathology. Research on FD and the identification of this pathology as a result of stem cell disease has allowed scientists to explore new therapeutic approaches based on the use of mesenchymal stem cells (MSCs). MSCs can be used to correct bone tissue disorders since they can differentiate into osteoblasts and promote bone tissue remodeling. This opens the possibility for MSC transplantation or modification of their functioning to restore bone structures affected by FD. In our opinion, one promising area is the study of the osteogenic activity of MSCs from pathological sites, as this may help develop new regeneration strategies. There is a limited number of studies indicating the potential for bone defect reconstruction through the combination of MSCs and allomaterial.